Technology Beneficiation Studies on Low-Grade Stibnite Ore of Chitral, NWFP, Pakistan: Beneficiation Studies on Low-Grade Stibnite (Biological Sciences - PJSIR, 2008)
Antimony ore of Chitral in North West Frontier Province (NWFP) of Pakistan, containing stibnite as an economical mineral, was upgraded by froth flotation technique. Through optimizing the flotation parameters, the grade of the final antimony concentrate produced was raised to 62% Sb with 95 % recovery.